2014
DOI: 10.3892/etm.2014.2047
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between ApoE gene polymorphisms and the occurrence of urolithiasis

Abstract: The aim of the present study was to investigate the correlation between apolipoprotein E (ApoE) gene polymorphisms and the occurrence of urolithiasis and dyslipidemia. A total of 180 Uyghur individuals, including 90 urolithiasis patients and 90 healthy controls, were enrolled in this study. The blood lipid profiles of the patients and controls were investigated and compared, and the composition of the urinary calculi was determined. The polymorphisms of the ApoE alleles were analyzed using polymerase chain rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The preliminary statistics of Kashi area in Xinjiang showed that the incidence of urolithiasis among Uighur children is higher than other ethnic group, accounting for 98% [ 3 ]. Clinical diagnosis has revealed that urolithiasis is more prevalent in Uighur patients than in patients of other races living in the same region [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The preliminary statistics of Kashi area in Xinjiang showed that the incidence of urolithiasis among Uighur children is higher than other ethnic group, accounting for 98% [ 3 ]. Clinical diagnosis has revealed that urolithiasis is more prevalent in Uighur patients than in patients of other races living in the same region [ 4 ].…”
Section: Introductionmentioning
confidence: 99%